Poder punitivo e a violação sistemática de direitos fundamentais: criminalidade e terrorismo na "era da informação" - Moreira Júnior, Ronaldo Félix (2016)
The work hereby presented deals with the complex issue of the rise of contemporary crime control and its impact within the digital scenario by working with assumptions about the (un)necessity to increase the punitive control in cyberspace. The aim of the work is the deconstruction of insecurity paradigm given to the virtual environment, as if it were a stage of action of dangerous criminals and terrorists. The scientific method adopted by the study is the materialist dialectic together with the bibliographic research technique in the fields of sociology and critical criminology. The theoretical framework in critical criminology is based on authors such as Eugenio Raul Zaffaroni, Juarez Cirino dos Santos, Mauricio Dieter Stegemann and Thiago Fabres de Carvalho; whereas in sociology the authors used were mainly: Ulrich Beck, Anthony Giddens, Zygmunt Bauman and Teresa Caldeira. The study starts with an explanation about the punitive power as a phenomenon intimately connected with the creation of figures to be stigmatized so that it can exercise its self-assertion. Thus, the first part focuses on performing an analysis of modernity and late modernity, according to sociological authors, pointing to the emergence of risks and trust in expert systems. The second part deals with the main criticisms directed at traditional criminology regarding the administration of crime in the contemporary scene, pointing out the criminal management not as an effective mean of reducing crime rates, but as a mean of administration and disposal of excluded groups. Moreover, it is woven an important critique of current attempt to reduce the complex phenomenon of terrorism to a purely criminal matter. Finally, the paper focuses its analysis to the cyberspace as a stage for systematic violations of fundamental rights through surveillance and also the exercise of punitive power in this environment, which has labeled new forms of virtual terrorism and crime as means to perpetrate their interests.